Relationship between parenting patterns with academic self-concept and school motivation in primary school students - Ordoñez Luna, Georgina (2024)
The education of students is affected positively or negatively by various factors such as the parenting patterns exercised by parents. The objective of this research was to identify the relationship between academic self-concept, school motivation and the type of parenting patterns perceived by children in the fourth, fifth and sixth grades of a primary school in the state of Tlaxcala, Mexico. The study was quantitative, cross-sectional and correlational, it was carried out during the 2022 school year. 213 students participated, with an age range of 8 to 12 years (M age 9.33, SD. = 0.802), the Motivation Scale was used. School, the Parenting Patterns Inventory and the Academic Self-Concept Scale. SPSS version 22 was used to analyze the data and the results showed two positive and significant associations between supportive parenting patterns, the first was with motivation (rs= 0.318**) and the second with academic self-concept (rs=0.303**), as well as between motivation and academic self-concept (rs= 0.289**). In the groups of students with coercive and indifferent parenting patterns, no associations were found between the variables. It is concluded that a supportive family environment that grants confidence promotes motivational factors and academic self-concept, in addition there is a close relationship between the perception one has as a student and motivation, which favors school performance, therefore, it is suggested conduct more research on this topic.